Comparative studies on storage cells in tardigrades during starvation and anhydrobiosis - Andy REUNER, Steffen HENGHERR, Franz Brümmer, Ralph O. SCHILL (Current Zoology, 2010)
The impact of starvation and anhydrobiosis on the number and size of the storage cells in the tardigrade species Milnesium tardigradum, Paramacrobiotus tonollii and Macrobiotus sapiens was investigated to gain more insight on the energetic side of anhydrobiosis. Storage cells are free floating cells within the body cavity of tardigrades and are presumed to store and release energy in form of glycogen, protein and fat to maintain a constant nutrient regime for the other tissues. The body size of the animals was not correlated with the size of the storage cells, however, M. tardigradum the largest species analysed also had the largest storage cells. A reduction in the size of the storage cells is apparent in all three species after seven days of starvation. A seven-day period of anhydrobiosis leads to a decrease in cell size in M. tardigradum but not in P. tonollii and M. sapiens. Although M. sapiens was raised on green algae, and M. tardigradum and P. tonollii were fed with rotifers and nematodes this difference in nourishment was not reflected in the response of the storage cells to anhydrobiosis [Current Zoology 56 (2): 259–263, 2010].